FOREIGN CAPITAL INFLOWS AND MANUFACTURING SECTOR GROWTH IN NIGERIA (Malaysian Management Journal, 2021)
The study examined the impact of foreign capital inflow on manufacturing sector growth in Nigeria using time series data from 1986 to 2019. The study specifically sought to examine the causal relationship between foreign capital inflows and the growth of the manufacturing sector in Nigeria in the long run The study employed the Autoregressive Distributed Lag (ARDL) estimation technique to account for the impact of foreign capital inflows on the manufacturing sector growth in Nigeria. The study utilized the Contribution of Manufacturing Sector to Gross Domestic Product (MGDP) as proxy for manufacturing sector growth. Manufacturing sector growth was the dependent variable while foreign direct investment (FDI), foreign portfolio investment (FPI) and foreign Aid (FOA) were the independent variables, and were regarded as proxies for foreign capital inflows. The study results revealed that foreign capital inflows through the FDI had a significant positive impact on contributions of the manufacturing sector to gross domestic product (GDP). The study also revealed that foreign capital inflows through the FPI had a significant positive impact on contributions of the manufacturing sector to the GDP. The study further revealed that foreign capital inflows through the FOA had a significant positive impact on contributions of the manufacturing sector to the GDP. Based on these findings, the study has recommended that the Nigerian government should promote foreign capital inflows through the FDI in order to achieve the desired level of manufacturing sector growth in the country’s economy in the long run. The government should also encourage foreign capital inflows through the FPI in order to attain the desired level of manufacturing sector growth in the Nigerian economy. Finally, the government should also support foreign capital inflows through the FOA in order to attain the desired level of manufacturing sector growth in the Nigerian economy in the long run.